A perspective on two pathways of photocatalytic water splitting and their practical application systems. Issue 9 (15th February 2023) - Ma, Yiwen; Lin, Lihua; Takata, Tsuyoshi; Hisatomi, Takashi; Domen, Kazunari
Abstract : This perspective presents the state-of-the-art of photocatalytic overall water splitting and the challenges toward large-scale applications. Abstract : Photocatalytic water splitting has been widely studied as a means of converting solar energy into hydrogen as an ideal energy carrier in the future. Systems for photocatalytic water splitting can be divided into one-step excitation and two-step excitation processes. The former uses a single photocatalyst while the latter uses a pair of photocatalysts to separately generate hydrogen and oxygen. Significant progress has been made in each type of photocatalytic water splitting system in recent years, although improving the solar-to-hydrogen energy conversion efficiency and constructing practical technologies remain important tasks. This perspective summarizes recent advances in the field of photocatalytic overall water splitting, with a focus on the design of photocatalysts, co-catalysts and reaction systems. The associated challenges and potential approaches to practical solar hydrogen production via photocatalytic water splitting are also presented.